Root rot induced by Phytophthora drechsleri Tucker, in cassava varieties - Lopes, Edson Batista; Matias, Edson Cavalcante; Aguiar Filho, Severino Pessoa de (Pesquisa Agropecuaria Brasileira, 2014)
Studies were realized in twenty five cassava varieties (Manihot esculenta Crantz), during the years 1976 and 1977, with the scope to study and to evaluate the damages caused by the fungus Phytophthora drechsleri Tucker, pathogenic agent responsible for cassava root rot. In field conditions the damages index was estimated to be 68.75%. It was advised the use of resistant varieties and the ridge planting system as measures of controlling this disease.